Specific identification of Campylobacter fetus by PCR targeting variable regions of the 16S rDNA - Oyarzabal, Omar A.; Wesley, Irene Varelas; Harmon, Karen M.; Schroeder-Tucker, Linda C.; Barbaree, James M.; Lauerman, Lloyd H.; Backert, Steffen; Conner, Donald E. (Veterinary Microbiology, 1997)
Campylobacter fetus is recognized as a human and animal pathogen. The isolation and differentiation of C. fetus in diagnostic laboratories is hindered by its relatively slow growth and lack of distinguishing biochemical characteristics. We developed a fast, reliable PCR assay that specifically amplifies a 554-bp segment of the 16S rDNA from C. fetus. Fifty-two ATCC reference strains and 255 bacterial field isolates comprising the genera Campylobacter, Arcobacter, Helicobacter, Escherichia, Listeria, Salmonella, and Wolinella were evaluated using this PCR protocol. Only, C. fetus strains were amplified. Sequence analysis of amplicons from ATCC and field strains of C. fetus confirmed the presence of the target DNA fragment. The detection limit of the technique was 5.9 x 103 CFU/ml. This PCR assay can yield reliable detection of C fetus within 3 h after isolation of presumptive colonies on agar plates.
Created from Fastlane, Scopus look-up
Keywords: 16S rRNA; Campylobacter fetus; Diagnosis-bacteria; PCR